LIMBAH CANGKANG KERANG HIJAU Ekonomi Sirkular di Pesisir: Studi Kasus Pemanfaatan Cangkang Kerang Hijau untuk Pakan Udang di Gresik: Ekonomi Sirkular di Pesisir: Studi Kasus Pemanfaatan Cangkang Kerang Hijau untuk Pakan Udang di Gresik - Leonard, Rikky; Dini Utami, Septaviola; Khilyatul Aulia, Prativi; Toto Wibowo, Alvalo; Sriwijayasih, Imaniah (PELITA NUSA TENGGARA, 2025)
The problem of coastal waste management in Gresik, especially green mussel shells, is a serious challenge that has an impact on the environment and the community's economy. This community service program aims to improve the circular economy in coastal areas, especially for residents of Banyuurip Village, Ujungpangkah, in the utilization of green mussel shells through Eco-entrepreneurship training based on the 3R principle. The community service program was carried out using a Participatory Action Research approach. The results of the community service program showed a significant increase of 65% in the behavior of recycling green mussel shell waste into shrimp feed, as well as increasing awareness in protecting the environment. This activity can create circular economic opportunities in coastal areas. This indicates that the community service program was successfully implemented through an environmentally based circular economy approach.